First evidence for the presence of amino acid sensing mechanisms in the fish gastrointestinal tract - Jessica Calo (Nature Portfolio, 2021)
Abstract This study aimed to characterize amino acid sensing systems in the gastrointestinal tract (GIT) of the carnivorous fish model species rainbow trout. We observed that the trout GIT expresses mRNAs encoding some amino acid receptors described in mammals [calcium-sensing receptor (CaSR), G protein-coupled receptor family C group 6 member A (GPRC6A), and taste receptors type 1 members 1 and 2 (T1r1, T1r2)], while others [taste receptor type 1 member 3 (T1r3) and metabotropic glutamate receptors 1 and 4 (mGlur1, mGlur4)] could not be found. Then, we characterized the response of such receptors, as well as that of intracellular signaling mechanisms, to the intragastric administration of l-leucine, l-valine, l-proline or l-glutamate. Results demonstrated that casr, gprc6a, tas1r1 and tas1r2 mRNAs are modulated by amino acids in the stomach and proximal intestine, with important differences with respect to mammals. Likewise, gut amino acid receptors triggered signaling pathways likely mediated, at least partly, by phospholipase C β3 and β4. Finally, the luminal presence of amino acids led to important changes in ghrelin, cholecystokinin, peptide YY and proglucagon mRNAs and/or protein levels. Present results offer the first set of evidence in favor of the existence of amino acid sensing mechanisms within the fish GIT.